Karakteristik Arus Lalu Lintas Pada Jalan 2/2 Tidak Terbagi - Sari, Yulianti Dewi Manda; Putra, Sasana; Sulistyorini, Rahayu; Herianto, Dwi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2023)
The conditions of volume, speed, and density are influenced by the interaction of the driver and the vehicle with the road and the environment. One of the way to understand traffic behavior is by describing it in mathematical and graphical form.Through analysis of the relationship between volume, speed, and density can be known information about the current traffic flow conditions. The Greenshield model is used to represent the mathematical relationship between volume, speed, and density. The purpose of the study to analyze the characteristic relationship on 2/2 roads with an undivided type. Based on the results of calculating the mean speed, the service level of this road is type E. The mean speed in the morning is 28.78 km/hour towards Teluk and 25.44 km/hour towards Tanjung Karang. It concluded that the mean speeds of vehicles at this research location are not according to the Regulation of the Minister of the Republic of Indonesia Number 96 of 2015, where for secondary arterial roads with a service level of at least C, namely 60 km/hour.Based on the analysis of the relationship between traffic characteristics using the Greenshield model obtained (r2) = 0,276.